Acanthamoeba genotype T4 detected in naturally-infected feline corneas found to be in homology with those causing human keratitis - Ithoi, I.; Mahmud, R.; Basher, M.H.A.; Jali, A.; Abdulsalam, A.M.; Ibrahim, J.; Mak, J.W. (2013)
A total of 10 out of 65 cornea swab samples from cats with eye symptoms showed Acanthamoeba-like morphology after cultivation. By PCR and DNA sequencing of Acanthamoeba diagnostic fragment 3 (DF3), all 10 isolates from the positive samples were categorized into two homologous groups of AfC1 (PM1, PM2, PM3, PF6, KM7, KF8, KMK9) and AfC2 (PM4, PM5, KFK10) due to the presence of bases A(354) and G(354), respectively. Furthermore, DF3 of AfC1 and AfC2 showed 100 similarity with Genbank reference isolates with the accession numbers DQ087314, EU146073 and U07401, GU808323, which were Acanthamoeba castellanii strains genotype T4 originating from human keratitis. This finding suggests that A. castellani strains have the capability to infect cats and human under favorable conditions.